Diagnóstico da meliponicultura no Estado de Rio Grande do Norte - Maia, Ulysses Madureira (2013)
Although stingless bee beekeeping (meliponiculture) is considered an established activity, widespread throughout Brazil, the practice is fundamentally traditional and technical knowledge is still scarce. In order to diagnose the current state of meliponiculture in Rio Grande do Norte, a region where the activity is very common, we interviewed 57 beekeepers scattered throughout the state. Structured questionnaires were used along with photographic records. The collected data allowed us to relate different management practices with production (honey and colonies) and income (generated from selling honey and colonies). Our results reveal that specific management practices can lead to higher productivity and generate a higher income, thus suggesting that an increased technification of meliponiculture could boost production and make the activity more profitable. Likewise, the presence of flowering plants around the sites where beekeepers keep the bees, and the ease of access to water, proved closely related to production and income. The data obtained here were compared with a previous census carried out in 2004, and with other similar studies from Brazil and other countries. This work pioneers a new kind of beekeeping diagnosis, highlights the need for technical improvement, and suggests measures to improve public policies